Public School Choice and Student Achievement: Evidence From Michigan's Interdistrict Open Enrollment System. (September 2017) - Cowen, Joshua M.; Creed, Benjamin
In this article, we focus on a statewide system of interdistrict open enrollment in Michigan, known as Schools of Choice. Our previous work indicated that students who take advantage of this program are disproportionately lower performing on state exams, come from lower-income families, and are more likely to be minority students. We estimated conditional bounds on these factors, as well as within-student variation in test scores, for the effect of participation in Schools of Choice, and find little evidence that student achievement is affected overall. We find little consistent evidence that subgroups of students based on race, gender or income benefit or lose disproportionately from the program, nor do students whose resident districts vary on key demographic or achievement characteristics.